The Diversity and Adaptive Evolution of Visual Photopigments in Reptiles - Katti, Christiana; Stacey-Solis, Micaela; Coronel-Rojas, Nicole Anahí; Davies, Wayne Iwan Lee (Frontiers in Ecology and Evolution, 2019)
Reptiles are a highly diverse class that consists of snakes, geckos, iguanid lizards and chameleons among others. Given their unique phylogenetic position in relation to both birds and mammals, reptiles are interesting animal models with which to decipher the evolution of vertebrate photopigments (opsin protein plus a light-sensitive retinal chromophore) and their contribution to vision. Reptiles possess different types of retinae that are defined primarily by variations in photoreceptor morphology, which range from pure-cone to rod-dominated retinae with many species possessing duplex (rods and cones) retinae. In most cases, the type of retina is thought to reflect both the lifestyle and the behavior of the animal, which can vary between diurnal, nocturnal or crepuscular behavioral activities. Reptiles, and in particular geckos and snakes, have been used as prime examples for the “transmutation” hypothesis proposed by Walls in the 1930s-1940s, which postulates that some reptilian species have migrated from diurnality to nocturnality, before subsequently returning to diurnal activities once again. This theory further states that these behavioral changes are reflected in subsequent changes in photoreceptor morphology and function from cones to rods, with a return to cone-like photoreceptors once again. Modern sequencing techniques have further investigated the “transmutation” hypothesis by using molecular biology to study the phototransduction cascades of rod- and cone-like photoreceptors in the reptilian retina. This review will discuss what is currently known about the evolution of opsin-based photopigments in reptiles, relating habitat to photoreceptor morphology, as well as opsin and phototransduction cascade gene expression.